Pengenalan dan Pemanfaatan Tanaman Penghasil Karbohidrat Non Beras dan Gandum sebagai Bahan Dasar Usaha Kuliner untuk Siswa Sekolah Menengah Kejuruan: Introduction and Utilization of Non-Rice and Wheat Carbohydrate Yield Plants as Based Materials for Culinary Business for Vocational High School Students - Mofit Saptono; Sri Endang Agustina Rahayuningsih; Ivone Christiana; Wijantri Kusumadati; Zahrotun Nafisah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Several carbohydrate source plants are well known to the people of Indonesia, seven of which are corn, bananas, sago, cassava, potatoes, sweet potatoes, and taro. Simultaneous efforts by introducing the potential of these plants to be used as culinary products is one thing that can be done. Vocational High Schools (SMK) with culinary expertise can help. Based on this, community service activities were carried out by a team from Palangka Raya University with a target of 40 students and teachers at SMK Negeri 3 Palangka Raya. Activities were carried out by outreach, consultation, interactive discussion, and hands-on practice of introducing and making cakes made from non-rice and wheat, as well as surveys of perceptions. This activity aims to provide socialization about non-rice and wheat carbohydrate source plants, nutritional value, and using safe chemicals for food. After this work was carried out, 51.40% of students were very satisfied, and 90.02% of students understood non-rice and wheat carbohydrate-producing plants and their processing. Students' understanding of the nutrition of non-rice and wheat commodities and the use of safe chemicals increased to 74.85% of the total number of students. Furthermore, guidance is needed so students can promote their culinary products and understand the flow of obtaining SPP-IRT.